(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
Laundry detergents are widely used in domestic, industry and other sectors everyday all over the world. It consists of different chemical components; surfactants, phosphate, builders, bleaches, optical brighteners, anti-redepositing agents, enzyme, perfume and color. Among these ingredients, surfactants and phosphate are considered as hazardous materials. With this view, composition, critical micelle concentration, and dissolved oxygen (DO) level in aqueous solution of some laundry detergents available in Bangladesh such as Chaka, Keya, Rin, Jet and Smart were determined and try to analyzed the chemical contribution of laundry detergents to pollute the environment. For Smart and Rin, the surfactant and phosphate amount were maximum, while it was minimum in Chaka and Jet respectively. The DO level was minimum in Smart and maximum in Jet. The results indicated that Jet is the effective laundry detergent in both cleaning and environmental aspect. Bangladesh J. Sci. Ind. Res. 52(4), 321-324, 2017